Bridging the Divide: A Systematic Review of the Theory–Practice Gap in Undergraduate Nursing Education - Makajil, Johari Daud (Education in Medicine Journal, 2026)
A persistent theory–practice gap exists in undergraduate nursing education worldwide, affecting students’ confidence, clinical competence, and preparedness for safe patient care. Although curriculum reforms and clinical learning experiences have been introduced, the mismatch between classroom-based knowledge and clinical practice remains a continuing challenge across nursing programmes. This systematic review aimed to synthesise current evidence on the theory–practice gap in undergraduate nursing education, with specific attention to students’ perceptions, contributing factors, and educational strategies used to reduce the gap. The review was conducted in accordance with the PRISMA 2020 guidelines. Three electronic databases, namely Scopus, PubMed, and Web of Science, were searched for peer-reviewed studies published between 2017 and 2024. Studies were included if they empirically examined the theory–practice gap among undergraduate nursing students. A narrative synthesis was conducted on 10 eligible studies. The findings indicate that the theory–several interconnected factors, including misalignment between curriculum content and clinical requirements, inadequate clinical mentorship, limited integration of simulation-based education, and insufficient collaboration between academic and clinical educators influence practice gap. Several educational strategies were identified, including high-fidelity simulation, reflective learning, participatory curriculum revision, and structured preceptorship models. However, challenges related to inconsistent implementation, resource limitations, and institutional coordination remain evident across settings. This review suggests that the theory–practice gap can be reduced through integrated nursing education that aligns academic content with authentic clinical practice. Strengthening academic–clinical partnerships, improving simulation-based learning, and supporting clinical educators are essential to prepare undergraduate nursing students to practise competently and confidently.